A novel role for follistatin in hypersensitivity following cystitis. Issue 2 (29th December 2015) - Shaffer, Amber D.; Feng, Bin; La, Jun‐Ho; Joyce, Sonali C.; Gebhart, G. F.
Abstract : Aims: Previous studies have shown that the activin‐binding protein follistatin reduces inflammation in several mouse models of colitis. To determine whether follistatin also has a beneficial effect following bladder inflammation, we induced cystitis in mice using cyclophosphamide (CYP) and examined the relationship between bladder hypersensitivity and bladder follistatin expression. Methods: Adult female C57BL/6 mice were treated with CYP (100 mg/kg) or vehicle (saline) three times over 5 days. Bladder hypersensitivity was assessed by recording the visceromotor response (VMR) to urinary bladder distension and in vitro single‐fiber bladder afferent recording. Follistatin gene expression was measured using qRT‐PCR. Immunohistochemistry was employed for further characterization. Results: Bladder hypersensitivity was established by day 6 and persisted to day 14 in CYP‐treated mice. On day 14, hypersensitivity was accompanied by increases in follistatin gene expression in the bladder. Follistatin‐like immunoreactivity colocalized with laminin, and the percentage of structures in the lamina propria that were follistatin‐positive was increased in CYP‐treated mice. Exogenous follistatin increased VMR and afferent responses to bladder distension in CYP‐ but not vehicle‐treated mice. Conclusions: Chronic bladder pain following CYP treatment is associated with increased follistatin expression in the bladder. These results suggest a novel, pro‐nociceptive role for follistatin in cystitis, in contrast with its proposed therapeutic role in colitis. This protein has exciting potential as a biomarker and therapeutic target for bladder hypersensitivity. Neurourol. Urodynam. 36:286–292, 2017 . © 2015 Wiley Periodicals, Inc.